Concrete masonry designer's handbook - Roberts, J. J. (Spon Press, 2001)
"The Concrete Masonry Designer's Handbook covers all aspects of the design, construction and performance of concrete masonry. Detailed chapters are provided on the principles of limit state design, materials and testing, and types of concrete masonry unit. Design guidance is provided on issues ranging from stability, robustness, loading, reinforcement and overall layout of walls. Additional design aspects are considered such as the thermal performance of masonry, the resistance of masonry to rain penetration, sound insulation, fire resistance and movement. Further practical help is provided on specification, workmanship, blemishes, and faults. Detailed cross-referencing is made throughout to the UK masonry design code BS5628."--BOOK JACKET.